A newest look at Argentina: "Diario austral", by Antonio Martínez Sarrión - Martí Monterde, Antoni (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
This article deals with a rather unknown aspect of the work of the newest writer Antonio Martínez Sarrión: his travel prose. While his poetry, diaries and memoirs have been studied, his travel book Diario Austral, published in 1987 at the Hiperión publishing house, has been out of print for many years and has never been republished. This work joins the tradition of Spanish travel writers in Argentina, adding a reflection on books and bookstores in the Argentine capital.